Aktivitas Antimikroba Dan Antioksidan Ekstrak Dan Fraksi Daun Tembelekan (Lantana camara L.) - Wahyuningrum, Retno; E, Genatrika; IN, Pahalawati (Jurnal Farmasi Udayana; Vol. 10, No 1, Tahun 2021DO - 10.24843/JFU.2021.v10.i01.p13, 2021)
Lantana camara  is a medicinal plant belongs to family Verbenaceae. It is widely used as traditional medicine for treating various health problems. But there has been no report about potential activity of L. camara that grow in Indonesia and its fractions. The aim of this research were to investigate the antimicrobial activity of extract and its fractions of L. camara leaves in against  . Extract was prepared by maceration in ethanol (96%) then fractionated using n-hexane and ethyl acetate. Antimicrobial activity was carried out using agar difussion method and antioxidant activity was carried out using DPPH radical scavenging activity assay. Concentration of extract and fraction tested were 12,5 ?g/mL; 25 ?g/mL; 50 ?g/mL; and 100 ?g/mL. The result showed that extract and fraction of L. camara leaves exhibit strong antibacterial activity against Gram positive bacteria ( Bacillus subtilis, Staphylococcus aureus ), weak inhibition against Gram negative bacteria ( Escherichia coli ), and and were not able to inhibit the growth of Candida albicans . The ethanolic extract of L. camara leaves and its fractions had antioxidant activity.  DPPH radical scavenging assay showed the IC50 value of 8.95 ?g / mL for ethanolic extract.